Relationship Lending and the Great Depression - Cohen, Jon; Hachem, Kinda; Richardson, Gary (The Review of Economics and Statistics, 2021)
Abstract The collapse of long-term lending relationships amplified the Great Depression. We demonstrate this by developing a new measure of lending relationships that can be calculated from widely available data at any level of aggregation. Our approach exploits differences in the responsiveness of loan rates to bank funding costs and is supported by historical evidence and theoretical arguments. The new measure reveals that the marginal impact of bank suspensions on economic activity was higher in more relationship-intensive areas, providing the first formal evidence that relationship lending propagated the real effects of banking sector distress in the early 1930s.